PERAN PENDIDIKAN AGAMA HINDU DALAM MEMBENTUK KEPRIBADIAN SISWA - Ni Kadek Santya Pratiwi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Children’s character building is a continuous effort with a strong foundation. The basis in question refers to the values developed in the environment where children grow and develop. The noble values that develop are derived from the values of religious teachings adopted by the students. Especially in Bali with the majority of Hindus, religious education has a major contribution to the formation of children’s character